Commercial agriculture and territorial resistance: Analysis of urban-rural relations in the province of Azuay - Rebai, Nasser (2013)
In the Ecuadorian province of Azuay, agro-ecology seems to signal towards the rebirth of family agriculture in a context of regional migration. Given changes in land usage and the improvement of peasant economies, we envisage a profound mutation in the rural landscape of Azuay. Notwithstanding, in lieu of a true model of territorial rural development, the term territorial resistance is used as weak regional commercial networks do not allow an adequate integration of a majority of peasants, evidencing the need for a more ambitious vision that takes into account the close ties between rural and urban areas, to assist the insertion of poor peasant farmers into commercial agriculture.